Performance analysis of a 3 phase 4 wire UPQC system based on PAC based SRF controller with real time digital simulation. (January 2016) - Patnaik, Nishant; Panda, Anup Kumar
Highlights: Power quality degrading issues are addressed under non ideal conditions of source and load using UPQC. Power angle control concept is used with SRF controller to manage sharing of reactive power compensation. Modified SVM technique and modified PLL method are adapted for smooth operation under unbalanced voltage conditions. Smooth and stable operation of UPQC system is observed for different transient conditions of load and voltage. Abstract: This paper proposes an advanced control technique for a 3 phase 4 wire UPQC system to tackle the major power quality issues such as voltage and current harmonics, sag & unbalanced voltage condition and unbalance condition in loads with high reactive power demand. The control system is based on PAC (power angle control) based SRF (synchronous reference frame) model with hysteresis current control and modified SVM (space vector modulation) technique for shunt and series APF parts of the UPQC system respectively. With this control approach, reactive power sharing feature between shunt and series APF can be accomplished without hampering the main functions of the UPQC under non ideal conditions. An elaborated performance analysis is carried out using MATLAB/SIMULINK software package along with real time investigation using RTDS (real time digital simulator).